Generation of high-energy neutrons with the 300-ps-laser system PALS. (1st June 2014) - Krása, J.; Klír, D.; Velyhan, A.; Krouský, E.; Pfeifer, M.; Řezáč, K.; Cikhardt, J.; Turek, K.; Ullschmied, J.; Jungwirth, K.
Abstract: The laser system PALS, as a driver of a broad-beam ion source, delivered deuterons which generated neutrons with energies higher than 14 MeV through the $\def \xmlpi #1{}\def \mathsfbi #1{\boldsymbol {\mathsf {#1}}}\let \le =\leqslant \let ≤ =\leqslant \let \ge =\geqslant \let ≥ =\geqslant \def \Pr {Pr}\def \Fr {Fr}\def \Rey {Re}{}^{7}Li(d, n){}^{8}Be$ reaction. Deuterons with sub-MeV energy were accelerated from the front surface of a massive $CD_{2}$ target in the backward direction with respect to the laser beam vector. Simultaneously, neutrons were emitted from the primary $CD_{2}$ target and a secondary LiF catcher. The total maximum measured neutron yield from ${}^{2}D(d, n){}^{3}He$, ${}^{7}Li(d, n){}^{8}Be$, ${}^{12}C(d, n){}^{13}N$ reactions was ${\sim } 3.5 ({± }0.5) × 10^{8}\ neutrons/shot$ .